Measuring the Capacity and Transaction Time of Cash and Electronic Toll Collection Systems - Karsaman, Rudy Hermawan; Mahendra, Yans; Rahman, Harmein; Sulaksono, Sony (ITB Journal Publisher, LPPM ITB, 2014)
A long queue can occur at tollgates due to the amount of transaction time required to perform ticket payment and toll fee collection. This problem can be addressed by the use of an electronic toll collection (ETC) system. A case study conducted on the Jakarta Intra Urban, Cikupa-Merak, and Cawang Pluit Toll Roads suggests that the queueing at the tollgates when modelled followed a Poisson distribution. The average cash transaction time was approximately 5 to 6 seconds, while the ETC transaction time was only 4 seconds. Furthermore, the capacity of the cash system gate was 550 to 620 vehicles/hour (which is above the minimum service standard of 450 vehicles/hour),whereas the electronic gate capacity was 770 to 870 vehicles/hour. This study demonstrates that the ETC system is more effective than the cash system in terms of reducing the number of queueing vehicles.